THE ROLE OF THE TEACHER IN CREATING INCLUSIVE SCHOOLS: A CASE STUDY IN A PRIMARY SCHOOL - Yahya, Rahmat; Widat, Faizatul; Ahmadi, Idris; Hina, Shahzadi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Inclusive education is an approach that aims to create an equal learning environment for all students, including students with special needs. At the elementary school level, the successful implementation of inclusive education is very dependent on the role of teachers in creating an atmosphere that supports the diversity and specific needs of students. This research aims to examine the role of teachers in realizing inclusive elementary schools, focusing on the challenges faced and the strategies implemented by teachers. The method used in this research is a literature review method, which examines various literature related to the role of teachers, inclusive education, and best practices in inclusive classroom management. The research results show that although challenges such as limited resources, lack of training, and social stigma are still obstacles, teachers have an essential role in creating inclusive learning through curriculum adaptation, using varied teaching methods, and building a school culture that supports diversity. This research also highlights the importance of ongoing training and support from schools and the community in helping teachers carry out their roles effectively.Keywords: Teacher Role, Inclusive Education, Inclusive Schools.